Pengaruh Pelatihan dan Kompetensi Terhadap Kinerja Karyawan PT XYZ - Elsela Arssyelina; Diyan Lestari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
World economic growth for two consecutive years continued to experience a slowdown, including Indonesia which experienced an economic contraction of up to 5.32% which had an impact on the tourism sector through important bussines sectors such as Travel Agent (PT XYZ) which also supports the tourism economy in Indonesia. This study was to determine the effect of training and work competence on employee performance at PT XYZ. There are still employees who lack the skills and competencies to meet their work needs, so PT XYZ must pay more attention to and maximaze the performance of its employees. This research is a quantitive research, distributing questionnaires to 76 respondents who are employees at PT. XYZ by using google forms.The method of data analysis was carried out using multiple linear regression. The results of this study indicate that training has an effect on employee performance. Work competence has an effect on employee performance.